Endoscopic revision of one-anastomosis gastric bypass (ER-OAGB) for weight recurrence: a case series of 17 adults - Daniel B. Maselli; Anna C. Hoff; Ashley Kucera; Areebah Waseem; Chase Wooley; Lauren L. Donnangelo; Brian Coan; Christopher E. McGowan (Therapeutic Advances in Gastrointestinal Endoscopy, 2023)
Weight recurrence after one-anastomosis gastric bypass (OAGB), the third most common metabolic and bariatric surgery performed worldwide, is observed in a subset of patients due to the chronic, progressive nature of obesity. Endoscopic revision of the OAGB (ER-OAGB) through full-thickness suturing to reduce the gastrojejunal anastomosis and gastric pouch is a potential alternative to surgical revision. Here, we present a case series of ER-OAGB and long-term nutritional support at two international centers with expertise in bariatric endoscopy. Data were retrospectively evaluated from a prospectively maintained database. The primary outcome was total body weight loss (TBWL) at 12 months. Secondary outcomes included TBWL at 3, 6, and 15 months; excess weight loss (EWL) at 3, 6, 12, and 15 months; frequency of new/worsening symptoms of gastroesophageal reflux disease (GERD); and the frequency of serious adverse events. In this series, 17 adults (70.6% female, mean age 46.8 years, mean BMI 39.1 kg/m 2 ) successfully underwent ER-OAGB an average of 8 years (range 2–21 years) after OAGB for a mean weight recurrence of 43.2% (range 10.9–86.9%). TBWL from ER-OAGB was 9.7 ± 1.8% at 3 months, 13.4 ± 3.5% at 6 months, 18.5 ± 2.1% at 12 months, and 18.1 ± 2.2% at 15 months. EWL from ER-OAGB was 30.5 ± 14.7% at 3 months, 42.6 ± 16.2% at 6 months, 54.2 ± 11.3% at 12 months, and 54.2 ± 11.7% at 15 months. There were no instances of new/worsening GERD symptoms or serious adverse events. In this small series of adults who experienced weight recurrence after OAGB, ER-OAGB facilitated safe and clinically meaningful weight loss, without new or worsening GERD symptoms, when performed by experienced bariatric endoscopists in concert with longitudinal nutritional support.